Evaluation of the Role and Success Factors of Facilitators in the Tenaga Kerja Mandiri Pemula (TKMP) Program: Case Study of Subang Regency - Nefan Satria Fajar Wengga; Harits Hijrah Wicaksana; Agung Edi Rustanto; Dani Lukman Hakim; Anthonius Whisnu Perdana Widiputra (Neo Journal of economy and social humanities, 2024)
Tenaga Kerja Mandiri Pemula (TKMP) is a program that was created as a source of competency improvement in training and provided financial assistance by the Ministry of Manpower as a step to reduce the number of unemployed as stated in Law Number 13 of 2023 concerning Manpower. This research aims to conduct a comprehensive evaluation of the role of facilitators in the Independent Beginner Employment program in Subang Regency and analyze various factors that influence the success of the role of companions. Qualitative methods were used with interview techniques with key informants of the TKMP program. This research uses qualitative methods by interviewing important informants who are directly involved in the program. The results can provide a comprehensive and in-depth picture of the role of assistants as well as suggestions for increasing the effectiveness of the TKMP program in Subang Regency in the future.